HTML5 games most wanted - Kuryanovich, Egor (Friends of ED, 2012)
"HTML5 Games Most Wanted gathers the top HTML5 games developers and reveals the passion they all share for creating and coding great games. You'll learn programming tips, tricks, and optimization techniques alongside real-world code examples that you can use in your own projects. You won't just make games--you'll make great games. dThe book is packed full of JavaScript, HTML5, WebGL, and CSS3 code, showing you how these fantastic games were built and passing on the skills you'll need to create your own great games. Whether you're a coding expert looking for secrets to push your games further, or a beginner looking for inspiration and a solid game to build on and experiment with, HTML5 Games Most Wanted is for you."--Publisher description